Surface Morphology and Chemical Changes of Maple and Beech Cut Through by CO2 Laser Under Different Angles Relative to the Wood Grain - Gurau, Lidia; Angelescu, Ana-Maria; Timar, Maria Cristina (MDPI AG, 2024)
This paper examined the surface morphology of maple and beech cut through by CO2 laser under different angles relative to the wood grain: 0◦, 15◦, 30◦, 45◦, 60◦, 75◦, and 90◦. In the analysis, stylus measurements, stereo-microscopic images, and chemical changes were considered. Laser uncovers more wood anatomical details, with enhanced clarity, when the cutting transitions from along the grain to across the grain. This is particularly noticeable in the earlywood and is more pronounced in maple compared to beech. The first tissue of earlywood was deeply ablated by the laser, leading to a wavy anatomical pattern, which is more visible for higher angles of laser cutting in relation to the wood grain. The anatomical structure of beech was more affected by carbonization in comparison to maple and had a significantly higher core roughness, Rk. For both species, the worst surface roughness occurred when cutting at 15◦. In maple, the laser caused more degradation of the polysaccharides compared to beech, and this impact was particularly noticeable parallel to the grain rather than at a 90◦ angle. The degradation of hemicelluloses occurred in parallel with more advanced cellulose degradation for beech compared to maple and for cutting along the grain compared to across the grain. Structural changes in lignin, such as condensation processes, were observed for both species.
Keywords: surface morphology; surface roughness; CO2 laser cutting; maple; beech; grain angle; microscopy; chemical changes